Analisis Konsumsi Daya dan Performa Pengunggahan dan Pengunduhan Data Pada Jaringan Ad-Hoc dan Jaringan Infrastructure Pada Raspberry Pi - Dhani Wahyu Wijaya; Rakhmadhany Primananda; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nowdays, there are a lot of research about IoT that connects multiple devices to communicate with other devices using wireless network and several sensors. The sensor depends on the source of the electrical power, it is a battery or power bank which has limited power capacity. The limitation of electric power capacity cause some problems, for the sensor Raspberry Pi which is expected to be able to survive as long as possible. Thus, it is studied to upload and download the data by Ad-Hoc network and Infrastructure in one room and some rooms to figure out network performance and power consumption. A tool to measure the voltage and current used is the USB Doctor Weight and the protocol that is used is SCP. In testing of uploading and downloading 32 MB, 64 MB and 128 MB data in one room resulted in better performance and more efficient power consumption in network infrastructure. While on uploading and downloading data in some rooms with data 32 MB and 64 MB remain more efficient on Infrastructure network but on 128 MB data have decreased performance. The results of the 128 MB data upload test with Ad-Hoc network require power 0,06548 Wh and the download require power 0,04802 Wh. Then on a 128 MB data upload with Infrastructure network require power 0,09294 Wh and the download require power 0,07745 Wh. The power consumption difference with 128 MB data on upload is 0,0275 Wh and download 0,02943125 Wh by using Ad-Hoc network. So it can be concluded that in the study upload and download data of 32 MB, 64 MB, in one room and in some rooms more power efficient through the network Infrastucture. While on the upload and download 128 MB data in some rooms more power efficient through the Ad-Hoc network, because the Infrastructure network decreased performance.